SUCCESSFUL SURGICAL MANAGEMENT OF TYPE III VAGINAL HYPERPLASIA IN A BREEDING LABRADOR RETRIEVER: A CASE REPORT - Ankush Kumar; Shivani Rohilla (Indian Journal of Veterinary and Animal Sciences Research, 2025)
Vaginal hyperplasia is a common reproductive disorder in intact female dogs, primarily occurring during the follicular phase of the estrous cycle due to elevated estrogen levels. This case report describes the successful surgical management of Type III vaginal hyperplasia in a nulliparous, one-year-eight-month- old Labrador Retriever, kept for breeding purposes. The dog was presented with a protruding vaginal mass and stranguria for 12 days. Clinical examination revealed a hyperemic, edematous, and ulcerated doughnut-shaped mass protruding from the vulvar rim. Hematological findings showed a mild leukocytosis, and vaginal cytology confirmed the late estrus stage. Given the need to preserve reproductive function, radical excision of the prolapsed vaginal mass was performed under general anesthesia, avoiding ovariohysterectomy. Postoperative care included antibiotic and analgesic therapy, wound management, and the use of an elizabethan collar. The patient exhibited an uneventful recovery, with normal urination restored the day after surgery. Histopathological examination confirmed vaginal hyperplasia without evidence of malignancy. The dog successfully conceived following estrus 25 weeks post-surgery, demonstrating the efficacy of surgical excision in maintaining reproductive potential. This case emphasizes the importance of individualized treatment strategies in breeding animals, ensuring both reproductive preservation and clinical resolution of vaginal hyperplasia.